A review of vertical farming technology: a guide for implementation of building integrated crop cultivation in agriculture sector / Nik Mohammad Shauqi Mohd ‘Arabi - Mohd ‘Arabi, Nik Mohammad Shauqi (Faculty of Plantation and Agrotechnology, 2019)
Vertical farming is a cultivation crops vertically by new agricultural method which combines with latest technology to produce the crops in large quantities. The vertical farming was introduced at the United States America (USA), New York on 1970 which is the people not have any land-use for the agriculture activities. Based on the paper review, there are have two method is vertical farming under control environment and natural system. In this study, technology as one of the important factors of vertical farming is discussed and reviewed by qualitative approach how to manage and instruct the vertical farm on right way. The others factor was encouraging to implement the vertical farms for the future where the limitation land-use, increasing the growth population of peoples and towards zero use of chemical in agriculture. The big problem is limitation of land-use for the agriculture sector. From the innovative makes, there are have three technique which is responsible to develop the crops in large quantities. It is hydroponic, aeroponic and aquaponic techniques. The main advantages of these technique cultivation system are saving of water and zero use of chemical which is using bio nutrient solution as fertilizer and light emitting diode (LED) as artificial light for growth where the chemical can give the risks and harmful to the human health for the long period. Besides, in this study, in an attempt to review the major opportunities and challenges of vertical farming and uses as the framework of sustainability to examine the role of it in prospective the food security to people’s stock.